Determinants of Serum Immunoglobulin Levels: A Systematic Review and Meta-Analysis - Khan, Samer R.; van der Burgh, Anna C.; Peeters, Robin P.; van Hagen, P. Martin; Dalm, Virgil A. S. H.; Chaker, Layal (Frontiers in Immunology, 2021)
Background: An up-to-date overview of determinants of serum immunoglobulins in adults is pivotal for clinical practice and research, but currently lacking. We therefore performed a systematic review and meta-analysis to identify determinants of serum immunoglobulin levels. Methods: Embase, Web of Science, Medline, Cochrane, and Google Scholar were searched from inception to July 11th, 2019 for articles reporting on determinants of serum immunoglobulin A, G or M (IgA, IgG or IgM) in adult humans. Random and fixed effect models were applied to obtain pooled mean differences (MDs) and 95% confidence intervals (CIs) for the association of age and sex with serum immunoglobulins. Results: We retrieved 117 articles reporting on determinants of serum immunoglobulins, of which 28 could be meta-analyzed. Older compared to younger individuals had higher IgA (MD: 0.38; CI: 0.18 ‒ 0.58), but lower IgM levels (MD: -0.40; 95%: -0.66 ‒ -0.14). Men had higher IgA (MD: 0.22; CI: 0.03 ‒ 0.42), but lower IgM levels (MD: -0.21; CI: -0.32 ‒ -0.10) than women. Age and sex did not influence IgG. Caucasian ethnicity was associated with lower IgA, IgG, and IgM. Smoking and corticosteroid use were associated with lower IgG. Positive associations were reported of probiotics with IgG, alcohol with IgA, hypertension with IgA and IgG, and acute psychological stress with IgA, IgG, and IgM. Conclusions: Older age and male sex are associated with higher IgA, but lower IgM, and urge investigation of age- and sex-specific reference ranges of immunoglobulins. Other identified determinants were ethnicity, diet, lifestyle and cardio-metabolic factors.